Distinguishing the offensive and defensive performances of starters and substitutes between high-level and low-level teams in elite women’s basketball games - Wenping Sun; LianYee Kok; ChenSoon Chee; Wensheng Xiao (PLoS ONE, 2025)
The primary goals of this study were to differentiate the offensive and defensive performances of starters and substitutes between high- and low-level teams in elite women’s basketball. This study examined 432 players from 36 women’s basketball teams who competed in the Tokyo Olympics, the 2022 Women’s Basketball World Cup, and the Paris Olympics. The rank-sum ratio was used to quantify and describe offensive and defensive performances of starters and substitutes, while the independent sample t -test, Pearson correlation, and Spearman Rho correlation were employed to test the differences and relationships between the various variables at a 0.05 level of significance. The results indicated that the offensive and defensive performances of both starters ( r = 0.932) and substitutes ( r = 0.848) had a significant correlation with the final rankings. Compared to high-level teams, low-level teams showed significant differences in points (p = 0.017), two-point (p = 0.015) and three-point (p = 0.000) shooting percentages, assists (p = 0.004), and steals (p = 0.040) for starters, as well as points (p = 0.033) and defensive rebounding (p = 0.027) for substitutes. Additionally, both starters and substitutes significantly correlated with points, two-point and three-point shooting percentages, defensive rebounds, and assists ( r > 0.600).